2017
DOI: 10.1177/0093854817714018
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Tablet-Based Psychological Tasks in Risk Assessment

Abstract: Risk assessment has become a prominent part of the criminal justice system in many jurisdictions, typically relying on structured questions and an interview. This approach, however, may not accurately assess certain psychological concepts correlated with reoffense, such as executive functioning, ability to plan, impulse control, risk-taking, aggression, and empathy. We hypothesized that using rapid-tablet-based neurocognitive tests would pay off in terms of objectivity, precision, and scalability when added to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…Previous psychometric evaluation of the NCRA suggested that predictors may exist that would correlate to specific crime subtypes, thereby increasing the predictive performance for a particular type of criminal offender (Ormachea et al, 2017). With increased sample size, we will apply the predictive model to criminal subtypes (e.g., arson, mass shooting) and hope to be able to draw connections between neurocognitive domains and more specific crimes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous psychometric evaluation of the NCRA suggested that predictors may exist that would correlate to specific crime subtypes, thereby increasing the predictive performance for a particular type of criminal offender (Ormachea et al, 2017). With increased sample size, we will apply the predictive model to criminal subtypes (e.g., arson, mass shooting) and hope to be able to draw connections between neurocognitive domains and more specific crimes.…”
Section: Discussionmentioning
confidence: 99%
“…Nonscored practice rounds were offered after the instructions, which included feedback to ensure the test-taker fully understood the instructions. The NCRA is comprised of seven tests (Figure 1), each of which was selected based on their relationship to reoffense, as detailed in the neurocognitive literature (Ormachea et al, 2017). The tests were then "gamified" (to benefit engagement and attention) and optimized to balance data collection against rapid testing time.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, of particular interest is the random assignment of offenders into different programme (Lerch et al, 2017) which found that computerised motivational intervention outperformed traditional probation regarding the treatment initiation rates at 2 months, although with diminished outcome at 6 months. Next, Ormachea et al (2017) wanted to know whether a computer game played by adult offenders could improve risk assessments using the Texas version of ORAS (Ohio Risk Assessment System). The research found that acute risk factors such as cognition, aggression and impulsivity, which are ordinarily more difficult to probe in face-to-face interviews, were more accurately assessed using the game.…”
Section: The Literaturementioning
confidence: 99%